2014
DOI: 10.1021/ac403174e
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Nitric Oxide Measurements from Donors in Cell Media: Identification of Scavenging Agents

Abstract: Nitric oxide (NO) is an essential messenger in human physiology, mediating cellular processes ranging from proliferation to apoptosis. The effects of NO are concentration dependent, and control over the instantaneous amount of NO available to cells is essential for determining the therapeutic NO dosages for various applications. As such, the development of NO therapeutic materials relies on accurate quantitative NO measurements that provide both total NO release from the NO donor as well as instantaneous NO co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…NO release from functionalized pεK contact lens gels (70 mg) was confirmed by chemiluminescence and profiles were obtained in three different solutions (all pH 7): phosphate buffer, cell culture media and LB broth (Figure ). This was to determine the NO release accurately under all experimental conditions as it has been reported that NO concentrations can differ in complex solutions such as cell culture media due to the presence of scavenging agents such as riboflavin and tryptophan that can potentially react with released NO. , In our experiments, the profile obtained in cell culture media was not significantly different to that measured in PBS alone. The maximum NO flux, [NO] m , in cell culture media was 2.27 × 10 –6 M compared to 2.35 × 10 –6 M in PBS.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…NO release from functionalized pεK contact lens gels (70 mg) was confirmed by chemiluminescence and profiles were obtained in three different solutions (all pH 7): phosphate buffer, cell culture media and LB broth (Figure ). This was to determine the NO release accurately under all experimental conditions as it has been reported that NO concentrations can differ in complex solutions such as cell culture media due to the presence of scavenging agents such as riboflavin and tryptophan that can potentially react with released NO. , In our experiments, the profile obtained in cell culture media was not significantly different to that measured in PBS alone. The maximum NO flux, [NO] m , in cell culture media was 2.27 × 10 –6 M compared to 2.35 × 10 –6 M in PBS.…”
Section: Results and Discussionsupporting
confidence: 91%
“…This is due to the low concentrations of riboflavin and tryptophan present in the media used in our study (0.58 × 10 −6 M and 44 × 10 −6 M respectively) and because the concentration of NO released was in excess of the concentration of scavenger. 42 In LB broth the [NO] m was 22% lower at 1.83 × 10 −6 M. This is in agreement with a study conducted by Reighard and Schoenfisch, who observed a 33% decrease in the amount of NO measured in LB broth due to scavenging of NO by proteins present in the broth. 43 The pεK contact lens gels released NO for in excess of 15 h, and the total NO ([NO] t ) released and measured in the three different solutions was 2.09 × 10 −3 , 2.02 × 10 −3 , and 1.70 × 10 −3 M in buffer, cell culture media, and LB, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, fluorescence counts were observed to be relatively lower when NOC13 was added to culture media but steadily increased over time; in contrast, fluorescence counts in PBS were higher but consistently plateaued after approximately 5 min (see Figs 1c,d, S2, S4 and S5). These differences are likely due to the inherent presence of NO producing or scavenging essential constituents in cell culture media 25 that are absent in PBS, but can affect the NOC13 degradation and the availability of NO to bind to [Ru(bpy) 2 (dabpy)] 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…The media employed to determine the NO release can affect the measurement as demonstrated by Schoenfisch's group 82 and Reynolds' group. 77 , 82 For this reason, we decided to perform the release in phosphate buffer, which has been demonstrated to give more accurate results.…”
Section: Resultsmentioning
confidence: 99%